Proposed A Design Knowledge-Based Performance Management Systems Framework In Pertamina University (The Indonesian Journal of Business Administration, 2021)
This year, the Ministry of Education and Culture is innovating by creating a transformation program aimed at universities. The innovation in this program is the establishment of eight Main Performance Indicators (IKU) that universities need to follow and fulfill. The method that universities can use in order to adapt to this program is to implement a Performance Management System (PMS). Most of the tertiary institutions do not have PMS which can present the eight Main Performance Indicators. Therefore, the aim of this research is to design PMS that have been integrated with the eight IKU from Ministry of Education so that it can make it easier for universities to achieve and fulfill these indicators. In this study, the college used as the object is Pertamina University. In this study, the PMS used was the Knowledge-Based Performance Management System (KBPMS). KBPMS has three perspectives, organizational output, internal processes and resource capabilities. This perspective is also divided into several aspects of the criteria and for KPIs that have been prepared by the Ministry of Education and Culture will be integrated into non-financial aspects from the perspective of organizational output.Keywords: Pertamina University, Performance Management System, “Indikator Kinerja Utama”, KBPSM